Short-term physical training enhances mirror system activation to action observation. (2nd January 2020) - Brunsdon, Victoria E. A.; Bradford, Elisabeth E. F.; Smith, Laura; Ferguson, Heather J.
ABSTRACT: The mirroring of actions is performed by a specialized system of neurons found in the sensorimotor cortex, termed the mirror neuron system. This system is considered an important mechanism that facilitates social understanding. We present a pre-registered experiment that used EEG to investigate whether short-term training via physical rehearsal or observational learning elicit distinct changes in mirror neuron activity for unfamiliar hand actions, and whether these training effects are influenced by the degree of familiarity (i.e., the frequency of action repetitions during training). Sixty adults completed a pre- and post-training EEG action observation task. Half of the participants completed 30 min of execution training (i.e., observing and performing unfamiliar hand actions), and half completed observation-only training (i.e., observing unfamiliar hand actions being performed). Post-training familiarity was manipulated by varying the number of training repetitions for each hand action (from 0 to 50 repetitions). Results revealed that sensorimotor cortex activity to the observation of hand actions increased following execution training, but did not change when training was simply observational. Moreover, the frequency of training repetitions did not modulate sensorimotor cortex activation after training, suggesting that short-term physical rehearsal enhances general processes involved in action understanding, rather than specific motor representations.